Type D Personality, Concomitant Depressive and Anxiety Disorders, and Treatment Outcomes in Somatic Symptom and Related Disorders: An Observational Longitudinal Cohort Study - de Vroege, Lars; de Heer, Eric W.; van der Thiel, Eva; van den Broek, Krista C.; van Eck van der Sluijs, Jonna F.; van der Feltz-Cornelis, Christina M. (Frontiers in Psychiatry, 2019)
Objective: To est